Utilisation of e-learning in the teaching of preclinical year students in a medical program / Effat Omar, Sabariah Abdul Rahman and Ariza Adnan - Omar, Effat; Abdul Rahman, Sabariah; Adnan, Ariza (UiTM Press, 2018)
Medical teaching is an apprentice-type training, where teachers and students have to physically meet in teaching and practice sessions. However, this notion is being challenged by introduction of virtual instructional methods. The present day students belong to Generation Y; they have high affinity for all things virtual since they have been introduced to this world from an early age. The aim of this paper is to describe the changes in utilization of virtual tools in teaching and learning of preclinical medical students in a public university. The trend of e-learning practices of lecturers teaching the pre-clinical years was observed over the last 5 years. Data was obtained through module guides, feedback during annual curriculum review and the changes observed in notional hours over the years. Results shown that the utilization of i-learn had drastically increase in the last 3 years. The usage was minimal in 2014/15; it reached full utilization for module preparation in 2015/16. This platform was used to provide module information as well as for posting learning material for tutorials, practical and directed self-learning sessions. All pre-clinical lecturers were familiar with i-learn format and training was provided as required. The use of other peripheral technologies, such as Facebook and twitter, were still limited, partly due to the opinion that students would be distracted by other content within this social media realm. As some of the contents were taught by virtual learning, face-to-face time was reduced.Hence, the utilization of e-learning the Faculty of Medicine UiTM was centered on using the university's learning management system.